Penegakan Hukum Dan Stigma Sosial Terhadap Anak Sebagai Pelaku Penyalahgunaan Narkotika Di Indonesia - Irma Nur Amanda; Dewi, Erna; Putri, Ria Wierma; Maroni, Maroni; Siswanto, Heni (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Restorative justice is an important approach in handling cases of drug abuse by children as an alternative to the repressive judicial system. This study analyses the effectiveness of its application in rehabilitation, education, and social reintegration, as well as identifying obstacles in the field through literature review and secondary data. The results show that diversion mechanisms and community-based rehabilitation programmes can reduce recidivism and social stigma. However, their implementation is still hampered by a lack of rehabilitation facilities, insufficient training for officials, and social stigma. Restorative justice has proven to be relevant for child protection, but requires stronger regulations, increased human resource capacity, and cross-sector collaboration to achieve sustainable results.